SOSIALISASI PEMILAHAN DAN PENGELOLAAN SAMPAH ORGANIK DI RW 12 BANDUNG INTEN - Putri Wijayanti, Anita (ABISATYA DINAMIKA ISWARA PUBLISHING, 2024)
Waste is one of Indonesia's biggest problems, especially in the city of Bandung. The biggest waste is generated from household waste. If this trash is left untreated, there will be a flood disaster in Indonesia. Community knowledge in RW 12 Bandung Inten about waste and its management is still minimal. For this reason, it is important to educate the public on how to sort and manage organic waste properly, as well as making residents aware not to just throw away waste without further consideration. Based on these problems, the aim of this community service activity is to provide a solution by educating the public about the importance of maintaining cleanliness and collecting and processing organic waste. If managed well, organic waste can be considered to have positive value. Compost can be made from organic waste, which can also be used as an alternative to artificial fertilizer. Apart from increasing soil fertility, compost is also produced through the use of organic waste. Traditional distribution of materials, demonstrations of household waste sorting activities, and conversations held to strengthen residents' understanding of the materials provided and demonstrations carried out are the approaches utilized in this PkM. activity. As a consequence of the PkM activities carried out on December 3 2023, the community showed concern for the importance of maintaining cleanliness, as well as increasing the community's understanding and knowledge of the process of sorting and processing organic landfill waste.